THE EFFECT OF PALEO-OCEANOGRAPHIC CHANGES ON THE SEDIMENTARY RECORDING OF HYDROTHERMAL ACTIVITY IN THE RED SEA DURING THE LAST 30,000 YEARS - Coulibaly A.S.; Anschutz P.; Blanc G.; Malaize B.; Pujol C.; Fontanier C. (My University, 2006)
The restricted exchange of water with the Indian Ocean makes the Red Sea extremely sensitive to global oceanographic changes, such as sea-level variations linked with Quaternary climate change. The 120 m global sea level lowering during the last glacial maximum caused great reduction in water exchange with the open ocean. At that time, salinities reached 50‰, and were beyond the tolerance of planktonic foraminifera. Some topographic depressions located on the Red Sea axial zone are the centre of hydrothermal activity. They are filled with hot brines and contain metalliferous sediments. We studied three sediment cores in the axial part of the Red Sea, one from the metal-rich Suakin Deep depression, and two cores sampled outside any deep, at two different depths. The sediment of the core located in the anoxic brine-filled Suakin Deep contained no benthic foraminifera, indicating the deep was filled by a brine pool during the recovered period of marine isotopic stages 1, 2, and 3. The distribution of benthic foraminifera in the two other cores indicates that Red Sea waters were saltier during stage 2 and 3 than today, and that at 2000 m depth, Red Sea waters were anoxic during stage 2 and dysoxic during stage 3. Profiles of Fe, Mn, and Zn indicate that the sedimentary flux of metals was higher during stage 1 than during stage 2 in hydrothermal brine-filled deeps. In contrast, the sedimentary flux of metal in cores outside the anoxic depressions was higher during stage 2. The shape of the metal profiles can be attributed to hydrological changes that induced variations of redox conditions in water column during isotopic stage 1, 2, and 3. During interglacial periods, metals dissolved in anoxic brines precipitated at the redox boundary that corresponded to the brine-seawater interface, so that metals precipitated only in the deeps. During glacial period, the deep water was anoxic, and the redox boundary was located above the brine-seawater interface. Therefore, the hydrothermal metals could diffuse into the anoxic deep Red Sea water and be precipitated over a large area. This interpretation suggests that the observed variations of metal concentrations are not only related to fluctuations of the hydrothermal fluid discharge, but also to the varying redox conditions in the deep Red Sea water. © 2005 Elsevier B.V. All rights reserved.
Keywords: GEOCHEMISTRY; HYDROTHERMAL; PALEO-OCEANOGRAPHY; PROXY; QUATERNARY; RED SEA; SEDIMENT; Cenozoic::Quaternary; Кайнозой::Четвертичная